ANALISIS PENGUATAN PERAN KELEMBAGAAN TERHADAP PENGENTASAN KEMISKINAN DAN PEMERATAAN PENDAPATAN DI INDONESIA - Lady Vironica Janiar; Aris Soelistiyo (Jurnal Ilmu Ekonomi JIE, 2017)
This study aims to determine how the role of institutions (government and banking) and the influence of the Provincial Minimum Wage, Rural Banks and Non-Performing Loan on poverty and income inequality in Indonesia in 2015-2016. This study uses panel data regression approach for 33 provinces in Indonesia during the 2015-2016 period. The result show that institutional role (government and banking) plays a strong role in poverty in 21 provinces and plays a week role in 12 provinces, and plays a strong role in income inequality in 12 provinces and plays a week role in 21 provinces. The result of the t test showed that the provincial minimum wage and rural banks a significant negative effect on poverty, and variable non-performing loan a not significant positive effect on poverty. While variable rural banks and non-performing loan a significant negative effect on income inequality, in addition to the provincial minimum wage positive and significant effect on income inequality. The result of the F test variable the minimum wage, rural banks, and  non-performing loan together effect on poverty and income inequality. When viewed from the estimation results can be seen that the R-squared value of 0,99 or 99% (Y1) and 0,98 or 98% (Y2). This means that 99% of poverty and 98% of income inequality in Indonesia is influenced by the provincial minimum wage (X1), rural banks (X2) and non-performing loan (X3). The remaining 0,01 or 1% and 0,02 or 2% is explained by other variables outside the model.Keywords: Poverty, Income Inequality, Provincial Minimum Wage, Rural Banks, Non Performing Loan